Russian and English idioms used for describing money (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article focuses on analysing Russian and English idioms with general meaning of money. Idioms are examined as a means of creating pragmatic impact and revealing the attitude of Russian and English native speakers to phenomenon of money.
Keywords: idiom; phraseosemantic model; money; pragmatic impact; fluctuation; discourse functioning